Stability Analysis of Finite Element Methods for the Acoustic Wave Equation with Absorbing Boundary Conditions (Part I) (Journal of Computational Mathematics, 1999)
In Part I and Part II of this paper initial-boundary value problems of the acoustic wave equation with absorbing boundary conditions are considered. Their finite element-finite difference computational schemes are proposed. The stability of the schemes is discussed and the corresponding stability conditions are given. Part I and Part II concern the first- and the second-order absorbing boundary conditions, respectively. Finally, numerical results are presented in Part II to show the correctness of theoretical analysis.